Efficacy of simulated video on test anxiety in objective structured clinical examination among nursing and midwifery students: A quasi‐experimental study - Ali Abbasi; Milad Bazghaleh; Nasrin Fadaee Aghdam; Mohammad Hasan Basirinezhad; Ahmet Tanhan; Rasoul Montazeri; Seyedmohammad Mirhosseini (Wiley, 2023)
Abstract Aim This research investigated the effectiveness of simulated video on test anxiety in the Objective Structured Clinical Examination (OSCE) among nursing and midwifery students. Design A quasi‐experimental study with a two‐group pre‐test and post‐test design. Methods This study was conducted on 118 nursing and midwifery students in Shahroud northeast of Iran in 2019 using the census sampling method. The intervention group received a 15‐minute OSCE simulation video half an hour before the test. Data were collected using the Sarason test anxiety questionnaire in two stages: one week before the test and after the simulation film was screened. Data were analysed using descriptive and inferential statistics (Independent t‐test, Chi‐square, Exact fisher and Paired t‐test). Results At baseline, no significant difference was observed between groups in the total mean score of test anxiety. The mean score of test anxiety significantly decreased in the OSCE simulation video group after the intervention.